1984
DOI: 10.1056/nejm198404123101503
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Trial of Methylprednisolone and Chlorambucil in Idiopathic Membranous Nephropathy

Abstract: Sixty-seven adults with idiopathic membranous nephropathy and the nephrotic syndrome were randomly assigned to symptomatic treatment only or to a six-month course of methylprednisolone alternated with chlorambucil every other month. Patients were followed for one to seven years. At the end of follow-up (mean of 31.4 +/- 18.2 months for the treated group and 37.0 +/- 22.0 for the control group) 23 of 32 treated patients were in complete or partial remission, as compared with 9 of 30 control patients (P = 0.001)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
109
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(115 citation statements)
references
References 15 publications
4
109
0
2
Order By: Relevance
“…A survey of all such trials reported between 1979 and 2001 revealed an extraordinarily low rate of thromboembolism (one case in Ͼ500 randomly assigned patients who were followed for Ͼ2000 patient-years). [23][24][25][26][27][28][29] Subtle selection forces operating at the enrollment level may have contributed to this finding. Natural history studies of untreated patients have also noted a low prevalence of thromboembolism in membranous nephropathy.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…A survey of all such trials reported between 1979 and 2001 revealed an extraordinarily low rate of thromboembolism (one case in Ͼ500 randomly assigned patients who were followed for Ͼ2000 patient-years). [23][24][25][26][27][28][29] Subtle selection forces operating at the enrollment level may have contributed to this finding. Natural history studies of untreated patients have also noted a low prevalence of thromboembolism in membranous nephropathy.…”
mentioning
confidence: 65%
“…A possible argument against "routine" prophylactic anticoagulants in idiopathic membranous nephropathy is that none of the randomized therapeutic trials in membranous nephropathy reported between 1979 and 2001 required that enrolled patients be routinely treated with prophylactic anticoagulants. [23][24][25][26][27][28][29] Because ethical considerations demand that participants in such trials receive standard of care, one would have to conclude that prophylactic anticoagulation of patients with membranous nephropathy (and by inference other patients with nephrotic syndrome) has not yet reached a uniform level of standard of care.…”
mentioning
confidence: 99%
“…The immunosuppressive recommendations for MGN based on RCTs include cyclophosphamide, chlorambucil, and cyclosporine regimens (5,18,(33)(34)(35). Most of these, but not all, concomitantly used corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…All but one were adults and were presenting a variable degree of proteinuria from 1 to 8 g/d. Patients with membranous glomerulonephritis (MGN) were receiving steroids as single drug (1 to 2 mg/kg) or in combination with immune suppressors (22); in some cases, ACEi (ramipril 5 to 8 mg/m 2 ) had been associated. Membrane Proliferative Glomerulonephritis.…”
Section: Patientsmentioning
confidence: 99%